Communal Land Conflicts as Contextual Social Studies Learning in West Sumatra - Refinaldi Refinaldi; Sumarni Sumarni; Muslim Muslim; Zulvia Trinova; Mahesa Putri Kencana (MASI Mandiri Edukasi, 2026)
Customary land conflicts in Indonesia reflect complex interactions among indigenous communities, the state, and economic actors, and offer meaningful learning opportunities for Social Studies Education. This study aims to analyze customary land conflicts as a source of social learning, legal awareness, and local wisdom-based education, and to develop a contextual Social Studies learning model. The research employed a qualitative approach using a single-case study design conducted in Kenagarian Kepala Hilalang, West Sumatra. Data were collected through in-depth interviews, participatory observation, and document analysis involving traditional leaders, local communities, and village officials. The findings reveal that customary land conflicts reflect real social dynamics marked by power imbalances, legal pluralism, and struggles for justice. Conflict experiences encourage reflective legal awareness, collective solidarity, and a deeper understanding of rights among indigenous communities. Minangkabau local wisdom, particularly deliberation, mutual cooperation, and restorative justice, plays a significant role in peaceful conflict resolution and in the transmission of values. Based on these findings, a conflict-based Social Studies learning model was formulated through stages of issue identification, actor analysis, value discussion, reflection, and social attitude formation to enhance students’ critical thinking, legal literacy, and civic responsibility.